2014
DOI: 10.4149/neo_2014_013
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and humoral immunodeficiency in breast cancer patients resistant to hormone therapy

Abstract: In view of the fact that insufficiency in immune response often correlates with poor prognosis, research in recent years has focused on the task of describing the precise status and function of the immune system and its possible effect on cancer patients. Although more than two thirds of treated patients respond to endocrine therapy, most patients with metastatic breast cancer develop a resistance to it. Estrogen modulates angiogenesis, partially through its effects on vascular endothelial growth factor (VEGF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In another study, it has been shown that VEGF is increased in plasmacytomas . Recently, it has been demonstrated that the levels of VEGF were increased in breast cancer patients resistant to hormone therapy, and this correlated inversely with the levels of serum immunoglobulins , indicating that there is probably a relation between VEGF levels, angiogenesis and impairment of humoral immunity. All the aforementioned data support our finding that immunoparesis may accompany solitary plasma cell tumors and, therefore, it could be a useful parameter for predicting evolution to MM.…”
Section: Discussionmentioning
confidence: 94%
“…In another study, it has been shown that VEGF is increased in plasmacytomas . Recently, it has been demonstrated that the levels of VEGF were increased in breast cancer patients resistant to hormone therapy, and this correlated inversely with the levels of serum immunoglobulins , indicating that there is probably a relation between VEGF levels, angiogenesis and impairment of humoral immunity. All the aforementioned data support our finding that immunoparesis may accompany solitary plasma cell tumors and, therefore, it could be a useful parameter for predicting evolution to MM.…”
Section: Discussionmentioning
confidence: 94%
“…It is still unclear how immune response genes are regulated in ER+ breast cancer cells and tumors. In breast cancer patients, depression in cellular immunity was associated with resistance to endocrine therapy [ 25 ]. In vivo models of mammary tumors suggest a role of immune-associated genes in antiestrogen resistance [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, TGF-β inhibits sphere-forming efficiency in MCF7 cells [ 65 ]. Treatment with TGF-β increases ALDH + and CD24 low /CD44 + CSC-enriched population in breast cancer cell lines [ 66 ] The plasma levels of TGF-β are upregulated in the group of these patients with endocrine-resistant breast cancer, as compare with the healthy group [ 67 ]. High PI3K and Hh pathway activity is relative to shorter PFS of metastases during tamoxifen treatment, and high TGF-β and PI3K pathway activity with worse response in treatment [ 68 ].…”
Section: Mechanism Of Endocrine Resistance In Breast Carcinomamentioning
confidence: 99%